Biogeochemical particle flux results of moored sediment trap systems from two long term mooring positions in the northern and southern Benguela Upwelling System between 2009 and 2023 - Luisa Chiara Meiritz; Tim Rixen; Anja K van der Plas; Tarron Lamont; Niko Lahajnar (PANGAEA, 2024)
The particle flux studies were carried out by the Biogeochemistry working group at the Universität Hamburg as part of the GENUS and TRAFFIC research projects. Two long term moored sediment trap systems (moorings, Sediment Trap from Hydrobios MST-12) were deployed between 2009 and 2023 during various research cruises with research vessels Meteor, Maria S. Merian, Sonne, Africana, Discovery and Mirabilis. The samples were described macroscopically and microscopically and separated into size classes <1 and >1 mm and then their dry weight was determined. The main components: total carbon (Ctot), total nitrogen (Ntot) and organic carbon (Corg) were then measured using an elemental analyzer (EuroVector Euro EA 3000). Total Flux is calculated as the total weight of the dried sample.